Comparative Analysis on Legislative Approaches on the Application of the Right to Work in the Republic of Moldova and the Danube Countries: Array - Roșca-Sadurschi, Ludmila; Ceclu, Liliana; Nedelcu, Ana (Journal of Danubian Studies and Research, 2020)
This research paper affirms that a high level of social and economic development at national level as well as a decent living of the population can be ensured through a secure and well-paid work. The right to work is considered one of the main rights in both national law and international conventions. In his context, this paper aims to perform a comparative analysis of normative acts issued in the Republic of Moldova and the Danube States (EU members) on the right to work as well as the social and economic results from the application of these normative acts. The authors expect to establish the logical link between legislation on labour-welfare and population-economic development of countries by conducting a comparative analysis of the provisions of regulatory documents, by observing and analysing statistical data on the economic and social situation in the analysed states. The results of this research will serve as a theoretical and applied basis for students, researchers, but also to formulate recommendations for the national legislature based on the successful experience of EU countries.